2020
DOI: 10.1177/2309499020918759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of medial and lateral tibial tunnel in pullout repair of posterior root tear of medial meniscus: Radiologic, clinical, and arthroscopic outcomes

Abstract: Purpose: Medial meniscus posterior root tear (MMPRT) should be repaired to the correct position as possible to maintain hoop tension of the meniscus. In this study, we propose a comparison of the outcome between the medial tunnel and the lateral tunnel in the pullout suture technique using the tibial tunnel for anatomical repair of posterior root tear of medial meniscus. Methods: From April 2010, of patients who underwent pullout suture, 51 cases (24 medial tunnel group (MTG) and 27 lateral tunnel group (LTG))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Among these patients, 49% saw progression of at least 1 K-L grade at a mean follow-up of 4.0 years (Figure 2). Eight of these studies reported mean joint space narrowing (2 did not 43,47 ), resulting in 32% of total patients being evaluated. The mean joint space narrowing for these patients was 0.64 mm at a mean follow-up of 4.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these patients, 49% saw progression of at least 1 K-L grade at a mean follow-up of 4.0 years (Figure 2). Eight of these studies reported mean joint space narrowing (2 did not 43,47 ), resulting in 32% of total patients being evaluated. The mean joint space narrowing for these patients was 0.64 mm at a mean follow-up of 4.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study 19 of the 11 reporting K-L grade progression recorded a P value that was statistically significant. However, 8 studies 15-17,19,37,43,46,48 performed Fisher exact tests on K-L grade distribution pre- and postoperatively. Five studies 15,16,37,43,48 demonstrated statistically significant changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 , 47 Kwon et al. 48 found that lateral tibial tunnel placement is more accurate and the tunnel is usually 5.6 mm medial to the root; by increasing our footprint, this lateral tunnel is placed centrally over the cancellous bone for a maximum healing surface, with the passage of sutures medial to the transition zone for improved repair strength. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Exposing bleeding cancellous bone in the line of the posterior horn of the medial meniscus, we aim to achieve stable healing of the root and improve stability of the meniscus by increasing the footprint under the red-red zone and location of the circumferential fibers to achieve ideal restoration of the hoop stress distribution without overconstraining the posterior horn movement. 41,47 Kwon et al 48 found that lateral tibial tunnel placement is more accurate and the tunnel is usually 5.6 mm medial to the root; by increasing our footprint, this lateral tunnel is placed centrally over the cancellous bone for a maximum healing surface, with the passage of sutures medial to the transition zone for improved repair strength. 49 The suture type and technique have been investigated comparing multiple iterations, although no studies to date have compared the suture location and combination of suture constructs and materials that we suggest using.…”
Section: Medial Meniscal Posterior Root Repair E23mentioning
confidence: 99%